Pluralisme Agama dalam sorotan Elit Agama di Malang Raya - Nasih, Ahmad Munjin; Sayono, Joko (LP2M, 2013)
Pluralismeagamatelahmenjadisalahsatuwacanakontemporeryangseringdibicarakanakhir-akhirabad20.Wacanainisebenarnyainginmenjem-batanihubunganantaragamayangbelakanganseringkalimenunjukkanwajahdisharmonisdenganbanyaknyakonflikyangmengatasnamakanagamasebagaisumberpermasalahannya.MalangRayasebagaisalahsatuwilayahyangmenjadipusatpengembanganagama-agamabesaruntukwilayahJatimmemilikipotensibesarterhadapmunculnyakonflikantarumat.Ataspertimbanganitulahpenelitianinidilakukan.AdapuntujuanpenelitianiniadalahmengungkaptentangpemahamanelitagamaIslamdarikalanganNUdanMuhammadiyahdalammemaknaipluralismeagamayangmeliputimaknapluralismeagamadanimplikasipluralismeagamaterhadapkeyakinanberagama.Selainitujugauntukmenjelaskanlangkah-langkahulamaNUdanMuhammadiyahdalammembangunharmonisasikehidupanberagamadanupayapencegahanterhadapkonflikkeagamaanyangmungkindisebabkanolehpluralitaspemahamankeagamaan.Metodepenelitianyangdipakaidalampenelitianinimenggunakanpendekatandeskriftifkualitatif.AdapunhasildaripenelitianinimenunjukkanbahwaadaperbendaanyangmendasarantarapemahamanelitNUdanMuhammadiyah.SecaraumumelitNUdapatmenerimapahampluralismeagamasementaraelitMuhammadiyahcenderungmenolak.ParaelitNUmembagipluralismaagamadalamduawilayahyakniwilayahteologisdansosiologis.Untukwilayahteologismerekamenolakakantetapisosiologismerekamenerimanya.